Proses Penyiapan Daging Hewan Kurban Tahun 1442 H di Kabupaten Manokwari, Yogyakarta dan Kota Magelang: Meat Preparation Process During The 1442H Eid Al Adha in The Manokwari Regency, Yogyakarta, And Magelang City - Isti Widayati; Dwi Nurhayati; Rizki Arizona; Alnita Baaka; John Arnold Palulungan; Wida W. Mubarokah; Priyo Sambodo (Fakultas Peternakan Universitas Papua, 2021)
Abstract This activity aims to determine the process of providing Eid al-Adha animal meat in Manokwari Regency, Yogyakarta and Magelang City. Observations of the process were carried out directly which included slaughtering until the meat was packaged in each of the 3 mosques located in Manokwari Regency, Yogyakarta and Magelang City. Data were analyzed descriptively and presented in tables and figures. The number of Eid al-Adha animals slaughtered was 59 cows and 96 goats/sheep with the highest number of Eid al-Adha animals in Yogyakarta. The process of preparing Eid al-Adha animal meat in Manokwari Regency and Magelang City is the same, which consists of slaughtering, peeling, chopping, weighing and packaging. Meanwhile in Yogyakarta there is carcass weighing before chopping. In general, the implementation of the process of preparing Eid al-Adha animal meat in Manokwari Regency, Yogyakarta and Magelang City has endeavored to meet the hygiene and sanitation aspects as an effort to obtain halal and thoyib (good) Eid al-Adha meat. Keywords: Preparation process; Eid al-Adha meat, Slaughter